2011
DOI: 10.1016/j.str.2011.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Galline Ex-FABP Is an Antibacterial Siderocalin and a Lysophosphatidic Acid Sensor Functioning through Dual Ligand Specificities

Abstract: SUMMARY Galline Ex-FABP was identified as another candidate antibacterial, catecholate siderophore binding lipocalin (siderocalin) based on structural parallels with the family archetype, mammalian Siderocalin. Binding assays show that Ex-FABP retains iron in a siderophore-dependent manner in both hypertrophic and dedifferentiated chondrocytes, where Ex-FABP expression is induced after treatment with proinflammatory agents, and specifically binds ferric complexes of enterobactin, parabactin, bacillibactin and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 47 publications
6
49
0
Order By: Relevance
“…Also, Correnti et al . (39) have found that siderocalin binding pocket mutants that cannot bind siderophores in vitro lose their bacteriostatic activity when added to bacterial cultures.…”
mentioning
confidence: 99%
“…Also, Correnti et al . (39) have found that siderocalin binding pocket mutants that cannot bind siderophores in vitro lose their bacteriostatic activity when added to bacterial cultures.…”
mentioning
confidence: 99%
“…Our calculations indicate that the cation-π interactions in pairs K125-Y132, F123-Lys134 and R81-W79, are energetically substantial enough (Table S1) to stabilize the holo-conformation of the protein. This is in addition to the cation-π bonds that were posited to occur with the ligand (9, 10). An alternative holo-conformation observed with a different ligand, carboxymycobactin T, (1×8U) is stabilized by the complementary cation-π in the pair R81-Y101 (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In lipocalins the study of cation-π interactions has been limited to two siderocalins, the neutrophil gelatinase-associated lipocalin (NGAL) and extracellular fatty acid binding protein (Ex-FABP). The analysis was restricted to the cation-π interaction in ligand recognition, i.e., only between ligand and protein side chains (9, 10). Here we will demonstrate that cation-π interactions within the protein can modulate ligand binding in a different way by stabilizing holo-form conformations in lipocalins.…”
mentioning
confidence: 99%
“…Ex-FABP is a 21 kDa lipocalin found in chickens [4,46]. The structural similarity to Scn, including a wide, positively charged calyx, prompted investigating the siderophore binding properties of Ex-FABP and the discovery that it is a siderocalin [47] (Figure 1).…”
Section: Ex-fabpmentioning
confidence: 99%